Legal obstacles facing Islamic banking in Malaysia - Hassan, Rusni; Muneeza, Aishath; Azzam Wajeeh, Ismail (World Business Institute, 2011)
Islamic banking is a concept which has proven itself to the world. Malaysia is considered as the cranium of Islamic banking and the rest of the world take lessons from Malaysia. The reason for this maybe because Malaysia is the first nation in the world to develop a sophisticated and a systematic legal infrastructure to welcome, develop and sustain Islamic banking parallel to the conventional banking in the country. The systematic and the dual banking approach adopted by Malaysia did gain the attention of the whole world. More than two and a half decades later, the question that still persists is what needs to be done for the sustainable development of Islamic banking in Malaysia? It is observed that without eliminating the legal obstacles facing Islamic banking in Malaysia, it would be impossible to sustain Islamic banking in the country. The main focus of the paper is to find out the legal obstacles facing Islamic banking in Malaysia.